Severe CD4(+) T-Cell Depletion in Gut Lymphoid Tissue during Primary Human Immunodeficiency Virus Type 1 Infection and Substantial Delay in Restoration following Highly Active Antiretroviral Therapy - Guadalupe, Moraima (American Society for Microbiology, 2003)
Gut-associated lymphoid tissue (GALT) harbors the majority of T lymphocytes in the body and is an important target for human immunodeficiency virus type 1 (HIV-1). We analyzed longitudinal jejunal biopsy samples from HIV-1-infected patients, during both primary and chronic stages of HIV-1 infection, prior to and following the initiation of highly active antiretroviral therapy (HAART) to determine the onset of CD4(+) T-cell depletion and the effect of HAART on the restoration of CD4(+) T cells in GALT. Severe depletion of intestinal CD4(+) T cells occurred during primary HIV-1 infection. Our results showed that the restoration of intestinal CD4(+) T cells following HAART in chronically HIV-1-infected patients was substantially delayed and incomplete. In contrast, initiation of HAART during early stages of infection resulted in near-complete restoration of intestinal CD4(+) T cells, despite the delay in comparison to peripheral blood CD4(+) T-cell recovery. DNA microarray analysis of gene expression profiles and flow-cytometric analysis of lymphocyte homing and cell proliferation markers demonstrated that cell trafficking to GALT and not local proliferation contributed to CD4(+) T-cell restoration. Evaluation of jejunal biopsy samples from long-term HIV-1-infected nonprogressors showed maintenance of normal CD4(+) T-cell levels in both GALT and peripheral blood. Our results demonstrate that near-complete restoration of mucosal immune system can be achieved by initiating HAART early in HIV-1 infection. Monitoring of the restoration and/or maintenance of CD4(+) T cells in GALT provides a more accurate assessment of the efficacy of antiviral host immune responses as well as HAART.